Structural and Optical Properties of Amorphous Al2O3 Thin Film Deposited by Atomic Layer Deposition - Shuzheng Shi; Shuo Qian; Xiaojuan Hou; Jiliang Mu; Jian He; Xiujian Chou (Advances in Condensed Matter Physics)
Aluminum oxide (Al2O3) amorphous structure with short-range order and long-range disorder has presented promising applications in optical and optoelectronic devices. In this paper, the Al2O3 films with different thickness were prepared by atomic layer deposition (ALD) technology at 200°C in order to achieve amorphous structure. X-ray diffraction (XRD) and energy dispersive spectrum (EDS) results indicated that the Al2O3 films were amorphous structure and stable O/Al ratio. The surface topography investigated by atomic force microscopy (AFM) showed that the samples were smooth and crack-free. Spectroscopic ellipsometer (SE) measurements were operated to investigate the effect of thickness on the structure and optical properties of films with Tauc-Lorentz model. It is found that the band gap exhibits a steady value ~2.3 eV by the UV-VIS transmittance method, but the T-L model was ~3.0 eV. The refractive index and extinction coefficient are related to the variation of thickness and the samples surface quality of amorphous network structure in the thin films. The outstanding optoelectronic properties and facile fabrication of Al2O3 films amorphous structure can be extended to other similar oxides, which could display wide applications in various engineering and industrial fields.